Gender Pay Discrimination In Lebanon, Assessment Of Recent Data - Dah, Abdallah (2010)
The factors relating to gender pay inequity have been studied extensively in the economics literature. This study examines the earnings differential between males and females in Lebanon utilizing a random sample that includes more than 17,000 Lebanese households. The results indicate that although a positive correlation exists between education level and income, females are still paid significantly less than their counterparts. Results also show that the gap in pay is not directly related to age. On the contrary, the gap in pay seems to have widened over time. This suggests that a targeted government policy is needed to reduce such inequity in the labor market of Lebanon.